Respon Imunoglobulin M dan Imunoglobulin G terhadap SARS-CoV-2 pada Dewasa - Geriko Y. Watupongoh; Fredine E. S. Rares; John P. Porotu'o; Sylvia R. Marunduh (Universitas Sam Ratulangi, 2021)
Abstract: The life of all people in the world has been affected since the COVID-19 hit the world at the end of 2019. In 2020 the whole world is faced with a very difficult year because the positive number of COVID-19 continues to grow. Even in Indonesia, COVID-19 is still a problem that affects various aspects of peopleâ€™s lives. Without being checked, someone who looks healthy can become one of the people without symptoms and continue to cause COVID-19 to spread in the community. The aim of this study was to determine the response of immunoglobulin M & immunoglobulin G to SARS-CoV-2 in adults. The results of the literature review study on Immunoglobulin M & Immunoglobulin G increased when there was exposure to SARS-CoV-2 , although other immunoglobulins also increased, the most visible and significant results in the diagnostic screening of COVID-19 were Immunoglobulin M & Immunoglobulin G. In conclusion, Immunoglobulin M & Immunoglobulin G has an increase in SARS-CoV-2 positive adults. Immunoglobulin M will appear early in symptom onset, and then two weeks after symptom onset Immunoglobulin G increases.Keywords: Immunoglobulin M, Immunoglobulin G, SARS-CoV-2, adults.Â Â Abstrak: Kehidupan masyarakat luas dipengaruhi sejak adanya COVID-19 yang melanda dunia pada akhir tahun 2019. Tahun 2020 seluruh dunia diperhadapkan dengan tahun yang begitu berat karena angka positif COVID-19 yang terus bertambah. Bahkan di Indonesia sendiri COVID-19 masih menjadi masalah yang mempengaruhi berbagai aspek kehidupan masyarakat. Tanpa dilakukan pemeriksaan seseorang yang terlihat sehat dapat menjadi salah satu orang tanpa gejala dan terus menyebabkan COVID-19 tersebar di masyarakat. Tujuan penelitian untuk mengetahui Respon Imunoglobulin M & Imunoglobulin G terhadap SARS-CoV-2 pada orang dewasa. Hasil penelitian literature review Imunoglobulin M & Imunoglobulin G meningkat saat ada paparan SARS-CoV-2, meskipun imunoglobulin lain juga ikut meningkat namun hasil pemeriksaan yang paling terlihat meningkat dan bermakna dalam screening diagnostik COVID-19 merupakan Imunoglobulin M & Imunoglobulin G. Sebagai simpulan, Imunoglobulin M & Imunoglobulin G mengalami peningkatan terhadap dewasa yang positif SARS-CoV-2. Imunoglobulin M akan muncul diawal gejala onset, dan kemudian dua minggu setelah gejala onset Imunoglobulin G meningkat.Kata Kunci: Immunoglobulin M, Immunoglobulin G, SARS-CoV-2, orang dewasa.